Knowledge, attitude, and practice on antibiotic use and antibiotic resistance among the veterinarians and para-veterinarians in Bhutan. - Karma Wangmo (Public Library of Science (PLoS), 2021)
Introduction Antimicrobial resistance is (AMR) an emerging global public health problem. Rationale use of antibiotic can prevent the rise of antimicrobial resistance. The objective of this study was to understand the knowledge, attitude and practice on antibiotic usage and AMR among the veterinarians and para-veterinarians in Bhutan. Method A cross-sectional questionnaire survey among the veterinarians and para-veterinarians was conducted from June to July 2020. A score of one to the correct answers and zero for the wrong answers was allotted to each respondent answers. The total score was added and those who scored above the mean was categorized as having good knowledge and favourable attitude. Result A total of 219 animal health workers participated in this study. The mean knowledge score was 12.05 ±1.74 with 38.8% of the respondents having good knowledge on antibiotic use and AMR. Similarly, the mean scores for the attitude level were 8.32±1.61 with 51% them having favorable attitude towards antibiotic usage and AMR. The mean practice score was 3.83±1.06 with 77% of them having good practices on antibiotic use. The respondents who read national plan on AMR were found to have good knowledge on antibiotics and AMR (AOR: 2.39; 95% CI: 1.19-4.82). The female respondents (AOR: 2.16; 95% CI: 1.01-4.61), respondents from the eastern region (AOR: 2.53; 95% CI: 1.18-5.44), west central (AOR: 3; 95% CI: 1.30-6.92), animal health supervisors (AOR: 9.77; 95% CI: 1.98-48.29), and livestock production supervisors (AOR: 2.77; 95% CI: 1.21-6.35) have favorable attitude towards antibiotics and AMR. Conclusions Our study identified that most animal health workers in Bhutan had poor knowledge on antibiotics usage and AMR. Therefore, regular awareness education on antibiotics and AMR in the form of refresher course/training must be provided to the animal health workers in the country to avoid inappropriate use of antibiotics.